2023
DOI: 10.1039/d2fo03861g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of simplified nonapeptides with broad-spectrum antimicrobial activities as potential food preservatives, and their antibacterial mechanism

Abstract: The nonapeptides 3IW (RIRIRIRWL-NH2) and W2IW (RWRIRIRWL-NH2) based on a β-pleated sheet template have potent broad-spectrum antimicrobial effects via membrane disruption and ROS accumulation, and show favorable preservative effects in chicken meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Subsequently, chicken breasts were divided into 1 g pieces and put into sterile centrifuge tubes, and the bacterial suspension (1 × 10 4 cfu/mL) was added at a ratio of 500 μL/g, followed by the addition of AMP to achieve a final concentration of 4 × MIC. Finally, all samples were immediately stored at 4 °C for 5 days, and then the number of bacteria in the different treatment groups was recorded daily …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, chicken breasts were divided into 1 g pieces and put into sterile centrifuge tubes, and the bacterial suspension (1 × 10 4 cfu/mL) was added at a ratio of 500 μL/g, followed by the addition of AMP to achieve a final concentration of 4 × MIC. Finally, all samples were immediately stored at 4 °C for 5 days, and then the number of bacteria in the different treatment groups was recorded daily …”
Section: Methodsmentioning
confidence: 99%
“…Finally, all samples were immediately stored at 4 °C for 5 days, and then the number of bacteria in the different treatment groups was recorded daily. 27 2.12. In Vivo Toxicity of 1018KI11.…”
Section: Application Of 1018ki11 In Chicken Breastmentioning
confidence: 99%
“…48 Yang et al reported on the antimicrobial activity of a set of nonapeptides designed based on the sequence RXRXRXRXL-NH by introducing different ratios (W : I = 1 : 3, 2 : 2, and 3 : 1) of aromatic residues (Trp, W) and branched-chain residues (Ile, I) in the X position. 49 They found that the presence of Trp at the 4th and 6th loci of the nonapeptide sequence facilitated the formation of a β-pleated sheet with a certain turn conformation, indicating that these two positions determine structural flexibility (Fig. 4a and b).…”
Section: Interaction With Bacterial Membranes – Design Rulesmentioning
confidence: 97%
“…Antimicrobial peptides (AMPs) have drawn a lot of attention as a treatment for germs that are resistant to numerous drugs. In the majority of multicellular organisms, antimicrobial peptides serve as the initial innate immune system defense [25,26]. Antimicrobial peptides serve as a crucial first line of defense for the body's immune system.…”
Section: Introductionmentioning
confidence: 99%